2015
DOI: 10.1007/s13311-014-0317-7
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Method for Inducing Nerve Growth via Modulation of Host Resting Potential: Gap Junction-Mediated and Serotonergic Signaling Mechanisms

Abstract: SummaryA major goal of regenerative medicine is to restore the function of damaged or missing organs through the implantation of bioengineered or donor-derived components. It is necessary to understand the signals and cues necessary for implanted structures to innervate the host, as organs devoid of neural connections provide little benefit to the patient. While developmental studies have identified neuronal pathfinding molecules required for proper patterning during embryogenesis, strategies to initiate inner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 125 publications
0
44
0
Order By: Relevance
“…; Blackiston et al. ), and it is tempting to speculate that neurotransmitters could play a conserved role as a layer of chemical signaling mediating between endogenous bioelectric gradients and downstream transcriptional cascades that regulate cell behavior and thus anatomy.…”
Section: Discussionmentioning
confidence: 99%
“…; Blackiston et al. ), and it is tempting to speculate that neurotransmitters could play a conserved role as a layer of chemical signaling mediating between endogenous bioelectric gradients and downstream transcriptional cascades that regulate cell behavior and thus anatomy.…”
Section: Discussionmentioning
confidence: 99%
“…Cell autonomous local bioelectric signaling has been observed in eye (Pai et al, 2012a) and brain (Pai et al, 2015) patterning, and is mainly transduced by intracellular calcium signaling and GJCs to regulate cellular behavior. Non-cell-autonomous bioelectric signaling has been observed in brain development (Pai et al, 2015), tumor suppression , ectopic innervation (Blackiston et al, 2015a), and left-right patterning (Levin and Mercola, 1999). While the transduction mechanisms of such effects are beginning to be understood, the extent of such signaling during normal development has not been explored.…”
Section: Membrane Voltage Potential Signals Over Long-distance Impingmentioning
confidence: 99%
“…Movement of serotonin through GJCs has also been shown to be an important component of distant bioelectric communication guiding ectopic nerve growth (Blackiston et al, 2015a). Finally, modeling and experimental testing of model predictions has revealed that the left and right sides of the Xenopus embryo produce a coherent long-range bioelectric growth-control signal that is coordinated by the action of GJCs .…”
Section: Bioelectric Signal Regulate Apoptosis and Proliferation Withmentioning
confidence: 99%
See 1 more Smart Citation
“…Work done in Xenopus and chick provides insight to this occurrence where serotonin (5‐HT), an endogenous neurotransmitter, establishes left‐right patterning in embryos through regulation of ion fluxes . A follow‐up study showed that extracellular 5‐HT availability drives innervation through tissues via gap junctional communication modulation . Combining their findings, Levin and colleagues propose that extracellular 5‐HT, a positively charged molecule, navigates through gap junctions to accumulate in hyperpolarized cells, mimicking the reuptake function of 5‐HT transporters (SERTs).…”
Section: Parallels Between Neurotransmission and Morphogen‐based Tranmentioning
confidence: 99%